The features of fruits drying in the production of natural chips - Husarova, Olena; Shapar, Raisa (Видавництво Львівської політехніки, 2017)
The objective of research was determination of the optimum heat treatment conditions before drying fruits and stage-wise dehydration modes. The optimal stage-wise regimes of apples drying in the production of fruit chips are presented in the article. The drying curves apples and organoleptic properties apple chips are analyzed. The obtained results were used in the development of energy-efficient technology for the production of fruit chips using the convection drying method, and the technical conditions were developed and approved. The developed technology increases the energy efficiency of the process by 15 %.
Keywords: fruit and vegetable chips; apple chips; thermal and humidity parameters of the drying agent; stage-wise drying; energy efficiency